Nivel de satisfacción de los clientes de Almacén Willian del cantón Santa Lucia - Suarez Choez, Ivonne Maritza (2020)
The present study is carried out in the Santa Lucia canton belonging to the province of Guayas, it is the level of satisfaction in the microenterprise of Mr. Willian Suárez said warehouse that is dedicated to the sale of footwear in general, it has been shown that in the 2 In recent years there was a low demand for the products offered due to the lack of knowledge about customer service, infrastructure, demonstrating the vital importance that both the owner and all the people working in this microenterprise know what are the benefits of achieving full satisfaction of the client, how to define it, take into account what levels of satisfaction are being produced, how to meet the expectations of the customers to penetrate the mind of the consumer and thus be better trained, to aim towards the desired goal.